2019
DOI: 10.1002/adsc.201901050
|View full text |Cite
|
Sign up to set email alerts
|

Double Hydroboration of Quinolines via Borane Catalysis: Diastereoselective One Pot Synthesis of 3‐Hydroxytetrahydroquinolines

Abstract: Described herein is an organoboranecatalysed consecutive borylative reduction of quinolines and isoquinolines to furnish tetrahydro(iso) quinolines bearing a C(sp 3 )À B bond β to the nitrogen atom. The installed CÀ B bond is oxidatively transformed to the hydroxy group in one pot. The present double hydroboration is proposed to proceed via a stepwise ionic mechanism involving a boronium ion. The stereo-outcome was found to be dependent on the position (C2 vs C4) of the substituents in quinolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…To this end, a B­(C 6 F 5 ) 3 -catalyzed reaction of 2,3-diphenylpyridine ( S1 ) was carried out in the absence of H 2 (Scheme a) . After reaction at 60 °C for 6 h, 1,4-dihydropyridine M1 , 1,2-dihydropyridine M2 , tetrahydropyridine M3 , and C3-borylated tetrahydropyridine M4 were obtained in 23%, 5%, 10%, and 2% yields (as determined by NMR spectroscopy), respectively, along with unchanged S1 . When the resulting mixture was treated with H 2 (3 MPa) and additional B­(C 6 F 5 ) 3 (5 mol %) at 80 °C for 20 h, P1 was obtained in 88% yield by NMR spectroscopy with an internal standard.…”
mentioning
confidence: 81%
“…To this end, a B­(C 6 F 5 ) 3 -catalyzed reaction of 2,3-diphenylpyridine ( S1 ) was carried out in the absence of H 2 (Scheme a) . After reaction at 60 °C for 6 h, 1,4-dihydropyridine M1 , 1,2-dihydropyridine M2 , tetrahydropyridine M3 , and C3-borylated tetrahydropyridine M4 were obtained in 23%, 5%, 10%, and 2% yields (as determined by NMR spectroscopy), respectively, along with unchanged S1 . When the resulting mixture was treated with H 2 (3 MPa) and additional B­(C 6 F 5 ) 3 (5 mol %) at 80 °C for 20 h, P1 was obtained in 88% yield by NMR spectroscopy with an internal standard.…”
mentioning
confidence: 81%
“…Hydrosilanes or hydroboranes were utilized as the milder reducing agents, [57–63] sometimes partially dearomative reduced quinolines were obtained. Recently, great progresses have been made in the catalytic dearomative reduction of quinolines by B(C 6 F 5 ) 3 and related Lewis acid analogues based frustrated Lewis pairs [64–70] . Chang and co‐workers have reported the cascade hydrosilylation of N ‐heteroarenes for synthesis of reduced N ‐heterocycles, which generally bear substituents in beta position with respect to the nitrogen atom (Scheme 1b(i)) [64,66,70] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great progresses have been made in the catalytic dearomative reduction of quinolines by B(C 6 F 5 ) 3 and related Lewis acid analogues based frustrated Lewis pairs [64–70] . Chang and co‐workers have reported the cascade hydrosilylation of N ‐heteroarenes for synthesis of reduced N ‐heterocycles, which generally bear substituents in beta position with respect to the nitrogen atom (Scheme 1b(i)) [64,66,70] . It is reported that for complete reduction of quinoline, excessive amounts of reducing agents and/or harsh conditions are still required to activate the dihydrogen and generate hydridoborate intermediate (Scheme 1b(ii)), [48,50] which is unfavorable for its practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In endeavors to achieve site-selective modifications of azacycles, transition metal catalysis has emerged as a powerful tool with the assistance of directing groups, while the approaches based on an organocatalyst are often limited in scope . Notably, tris­(pentafluorophenyl)­borane, B­(C 6 F 5 ) 3 , has been appreciated as a versatile catalyst toward various types of N-heterocycle transformations. For instance, Wasa, , Paradies, and Wang have independently reported borane-catalyzed α-alkylation of organoamines by trapping iminium intermediates with alkenes (Scheme a, top). Our group previously showed that B­(C 6 F 5 ) 3 catalyzed a cascade process of β-silylation of N-arylpiperidines via enamine intermediates (Scheme a, bottom) …”
mentioning
confidence: 99%
“…According to the above experimental and computational rationale as well as the precedents, ,− ,, a reaction pathway of the B­(C 6 F 5 ) 3 -catalyzed cine -silylative ring-cleavage of α-methyl azacycles is depicted in Scheme . We propose that the overall transformation involves five-step cascade processes: (i) reversible exo -dehydrogenation of α-methylpiperidine 1a to enamine via consecutive α-hydrogen abstraction and β-deprotonation; ,,, (ii) rate-limiting liberation of H 2 from [ 1a -H + ]­[(C 6 F 5 ) 3 BH – ] salt (Δ G ⧧ = 35.2 kcal/mol, see the Supporting Information for details); ,,, (iii) hydrosilylation of enamine to form β-silylpiperidine; , (iv) ring-opening C–N bond cleavage enabled by cis -β-amino elimination of a 2-silazetidinium intermediate leading to N -silylaminoalkene; , and (v) β-selective hydrosilylation of the olefin to give final product 3 …”
mentioning
confidence: 99%